2011
DOI: 10.1002/pat.1543
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of novel silica modified polyimide membranes: synthesis, characterization, and gas separation properties

Abstract: In this study, new monomers having siloxane groups were synthesized as an intermediate for preparation of siloxane modified polyimide polymers. Then with these monomers, the synthesis of uncrosslinked and crosslinked polyimide–siloxane hybrid polymer membranes were achieved. The purposes of the preparation of modified polyimides were to modify the thermal and chemical stability, and mechanical strength of polyimides, and to improve the gas separation properties of polymers. The new diamine monomer having silox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…With regard to the increase of the diffusion coefficient, Boroglu et al reported that the permeability coefficient of polyimide-siloxane hybrid membranes increased with increasing the siloxane content. And they suggested that the increased gas permeability resulted from the large enhancements of mean size and total amount of free volume holes attributed to the loose Si-O-Si networks and the crosslinked structure of the hybrid membranes [28]. The increased solubilities suggest that the Langmuir sorption site is additionally formed by the incorporation of silica domains.…”
Section: Gas Transport Propertiesmentioning
confidence: 99%
“…With regard to the increase of the diffusion coefficient, Boroglu et al reported that the permeability coefficient of polyimide-siloxane hybrid membranes increased with increasing the siloxane content. And they suggested that the increased gas permeability resulted from the large enhancements of mean size and total amount of free volume holes attributed to the loose Si-O-Si networks and the crosslinked structure of the hybrid membranes [28]. The increased solubilities suggest that the Langmuir sorption site is additionally formed by the incorporation of silica domains.…”
Section: Gas Transport Propertiesmentioning
confidence: 99%
“…Similar polyimides containing siloxane pendant groups, reported previously, showed two transition temperatures being the first one associated to Si-O-Si ligands, and the second one related to the rigid aromatic structure [29]. However, the length of siloxane pendant groups in PI-Si was not enough to allow phase segregation and only one glass transition has been observed.…”
Section: Resultsmentioning
confidence: 86%
“…The solid state 29 Si-NMR spectrum with cross polarization and magic-angle spinning of PI-Si revealed an unexpected alkoxysiloxane structure in the polymer after hydrosilylation with DMES. The appearance of two signals at -9.62 and -20.59 ppm (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We define the terms of "hybrid" and "composite" as following: "hybrid" materials are those that have strong chemical interaction between organic and inorganic components such as covalent bonds, and "composite" materials are those that show weak or no interactions between the two components. Synthesizing polyimide-silica hybrid and composite materials and investigating their physical and gas transport properties have also received much attention [4][5][6][7]. Polyimide-silica hybrids and composites can be prepared by sol-gel processes or the addition of colloidal silica.…”
Section: Introductionmentioning
confidence: 99%